1985
DOI: 10.1063/1.555750
|View full text |Cite
|
Sign up to set email alerts
|

The Electronic Spectrum and Energy Levels of the Deuterium Molecule

Abstract: Beginning in the 1930s, G.H. Dieke and his students carried out an extensive program of measuring the optical spectrum of molecular hydrogen and its isotopes. Parts of the work were published but the project was interrupted by Dieke’s death in 1965, with much of the latest and most accurate work unpublished. This paper gives the 27 488 lines of molecular deuterium, measured by Dieke, arranges the 8243 assigned lines into band systems, and derives rotational–vibrational energy levels for over 50 electronic stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

19
154
6
3

Year Published

1990
1990
2013
2013

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(182 citation statements)
references
References 0 publications
19
154
6
3
Order By: Relevance
“…Observed transition frequencies over the full depth of the potential wells of the B 24 and Abgrall et al 21 observed only vibrational levels v = 0-18.…”
Section: Resultsmentioning
confidence: 93%
See 2 more Smart Citations
“…Observed transition frequencies over the full depth of the potential wells of the B 24 and Abgrall et al 21 observed only vibrational levels v = 0-18.…”
Section: Resultsmentioning
confidence: 93%
“…38,39 In a study of the emission spectrum of D 2 , the existing potentials were semi-empirically optimized by fitting to line intensities and line positions in the spectrum, resulting in a slightly deviating potential energy curve. 21 Experimental line positions were taken from the analysis by Freund et al, 24 who analysed the extensive emission dataset from Dieke's laboratory group. In Fig.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…16, where the measured spectrum right before and after the gas puff is shown for the outermost view (ρ ≈ 1.04) of the LFS poloidal periscope. For illustration, the position of tabulated molecular deuterium lines 42 The parts of the spectra outside the wavelength region of the Boron lines can be used to detect the presence of D 2 lines. One can then exclude these spectra in the analysis.…”
Section: B Contamination By Molecular Linesmentioning
confidence: 99%
“…This permits unperturbed measurements with these LOS also during edge-instabilities. 25 are shown that correspond to n = 3 → 2 transitions of the D2 triplet system.…”
Section: B Edge-d-alpha Radiationmentioning
confidence: 99%